PEGylated poly(ester amide) elastomers with tunable physico-chemical, mechanical and degradation properties. (November 2015) - Xue, Yingfei; Patel, Akhil; Sant, Vinayak; Sant, Shilpa
Graphical abstract: PEGylated poly(ester amide) biodegradable thermoset elastomers largely broaden the important properties for tissue engineering application. Highlights: A new class of elastomers has a wide range of mechanical and degradation properties. PEG incorporation to APS improved pre-polymer solubility and processability. APS- co -PEG biodegradable thermoset elastomers showed good cytocompatibility. APS- co -PEG biodegradable elastomers may be suitable for soft tissue engineering. Abstract: Biodegradable synthetic elastomers such as poly(1, 3-diamino-2-hydroxypropane- co -polyol sebacate)s (APS) are gaining importance in soft tissue engineering applications due to their biocompatibility and mechanical compliance. However, APS-based thermoset elastomers possess narrow spectrum of physicochemical and functional properties, limiting their biomedical applications. In this study, we overcome these limitations by incorporating biocompatible polyethylene glycol (PEG) into the polymer backbone. A series of novel APS- co -PEG copolymers were synthesized by varying PEG mole percentage (15–40%) and PEG molecular weight (400 Da to 4 kDa) to tune the physicochemical, mechanical and degradation properties. APS- co -PEG pre-polymers were characterized by nuclear magnetic resonance ( 1 H NMR), Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC) and differential scanning calorimetry (DSC). The pre-polymers were thermally crosslinked into copolymer films and characterized for mechanical and degradation properties. Solubility of APS- co -PEG pre-polymers in common organic solvents was significantly improved by incorporation of PEG. Changes in molar percentage and molecular weight of PEG, monomer feed ratio and crosslinking time resulted in a wide range of ultimate tensile strength (0.07–2.38 MPa), elastic modulus (0.02–3.0 MPa) and elongation (93–993%) in crosslinked APS- co -PEG films. PEG incorporation increased the hydration of APS- co -PEG films, leading to tunable degradation rates (10–40% mass loss over 14 days). APS- co -PEG films also supported cell proliferation. The broad spectrum of properties exhibited by this novel series of elastomers indicates their promise in potential applications for soft tissue engineering.